2021
DOI: 10.3389/fonc.2021.781471
|View full text |Cite
|
Sign up to set email alerts
|

The Circ_0001367/miR-545-3p/LUZP1 Axis Regulates Cell Proliferation, Migration and Invasion in Glioma Cells

Abstract: Glioma is the most common primary intracranial malignant tumour in adults. It has a high incidence and poses a serious threat to human health. Circular RNA is a hotspot of cancer research. In this study, we aimed to explore the role of circ_0001367 in gliomagenesis and the underlying mechanism. First, qRT-PCR was conducted, which showed that circ_0001367 level was downregulated in glioma tissues and cells. Next, gain-of-function and loss-of-function assays were performed, which indicated that circ_0001367 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Forty-five articles examining the p53 pathway were included which reviewed the mechanisms to reactivate and enhance tumour suppressor activities of p53. For cell migration, our search yielded 13 articles which met the inclusion criteria and discussed the use of the actin cytoskeleton and MMP to promote cell migration in GBMs [ 46 , 47 , 48 ]. There is a significant role of RNA–long non-coding, micro or circular to regulate cell motility; downregulation of specific RNAs can suppress migration.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five articles examining the p53 pathway were included which reviewed the mechanisms to reactivate and enhance tumour suppressor activities of p53. For cell migration, our search yielded 13 articles which met the inclusion criteria and discussed the use of the actin cytoskeleton and MMP to promote cell migration in GBMs [ 46 , 47 , 48 ]. There is a significant role of RNA–long non-coding, micro or circular to regulate cell motility; downregulation of specific RNAs can suppress migration.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unknown why cells have the unnecessary delay in contraction during cytokinesis via LUZP1. Recent studies have reported that LUZP1 expression is downregulated in several types of cancer and that LUZP1 can suppress the proliferation of some cancer cells (Dong et al, 2021; Bozal-Basterra et al, 2021). These findings suggest that LUZP1 may contribute to genome stability by preventing a failed chromosome distribution by delaying cytokinesis.…”
Section: Discussionmentioning
confidence: 99%
“…1A; Lee et al, 2001; Sun et al, 1996; Wang and Nakamura, 2019). The protein function of LUZP1 has long been unknown, but it is becoming rapidly apparent: LUZP1 mainly localizes to the actin filaments and stabilizes the actin cytoskeleton (Gonçalves, 2022; Wang and Nakamura, 2019); LUZP1 localizes at the centrosome and restricts primary cilia formation (Bozal-Basterra et al, 2020; Gonçalves et al, 2020); embryos of LUZP1 null knockout (KO) mice display cardiovascular and cranial defects with prenatal death (Hsu et al, 2008); LUZP1 genomic aberrations are detected in several types of cancer and syndromes (Bhat et al, 2022; Bozal-Basterra et al, 2021; Dong et al, 2021; Edwards et al, 2019; Poel et al, 2019; Zaveri et al, 2014); And LUZP1 interacts with microtubule and various other proteins and complexes (Fig. 1A; Krebs et al, 2010; Liu et al, 2017; Niri et al, 2021; Yano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] Considering the “sponge” effect of circRNAs, we further sought the downstream miRNA related to circ_0018909 in pancreatic cancer. The previous research illustrated that miR‐545‐3p functioned as the downstream of circ‐IFT80, circ_0072083, and circ_0001367 to modulate endometrial cancer, [ 43 ] glioma, [ 44 ] and nonsmall cell lung cancer [ 45 ] progression. In this paper, miR‐545‐3p inhibition harbored the suppressive action of circ_0018909 deficiency on cell metastasis, EMT, and growth, as well as the facilitating impacts on apoptosis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%